Competition for firms in an oligopolistic industry: do firms or countries have to pay? - Andreas Haufler; Ian Wooton (Center for Economic Studies and ifo Institute (CESifo), 2007)
We set up a model of generalised oligopoly where two countries of different size compete for an exogenous, but variable, number of identical firms. The model combines a desire by national governments to attract internationally mobile firms with the existence of location rents that arise even in a symmetric equilibrium where firms are dispersed. As economic integration proceeds, equilibrium taxes decline, switching from positive to negative levels, and then rise as trade costs fall even further. A range of trade costs is identified where economic integration raises the welfare of the small country, but lowers welfare in the large country.
Keywords: H25; H73; F15; F23; 330; Direktinvestition; Steuerwettbewerb; Subvention; Standortwettbewerb; Oligopol; Wirtschaftsintegration; Wohlfahrtseffekt; Zwei-Länder-Modell; Theorie